Land degradation neutrality and carbon neutrality: approaches, synergies, and challenges - Gunawardena, M. Amritha; Lokupitiya, Erandathie; Gunawardena, Prasanthi (Frontiers in Forests and Global Change, 2024)
Land is being degraded rapidly worldwide. United Nations Convention to Combat Desertification in 2015 has invited countries to formulate voluntary targets to achieve Land Degradation Neutrality (LDN). Under the Paris Agreement, a legally binding international treaty adopted in 2015, the world is transitioning toward Carbon Neutrality (CN) with more mitigation actions. This paper intended to review the concepts of land degradation, LDN along with CN emphasizing the degradation types, approaches, models available to analyze, synergies, economic aspects and challenges. The review explores approaches and models available for achieving LDN and CN which are both synergistic, economically efficient and could overcome the common challenges. Land degradation has to focus beyond the traditional definitions to incorporate more persistent and the difficult to restore degradation causes. Such complex land degradation requires specialized LDN approaches. The level of degradation and restoration progress could be analyzed using a variety of modeling approaches including economic models. Approaches for LDN and CN can bring significant synergies for each other. The approach proposed by the present study will provide a logical flow for decision-making while minimizing time and effort and avoiding a piecemeal approach. The approach therefore maximizes the output in relation to the inputs thus enhancing sustainability.